Cultural Intelligence Effect on Job Satisfaction over Employee Performance - Syuman Takdir; Tantri Yanuar Rahmat Syah; Rina Anindita (Journal of Multidisciplinary Academic, 2020)
The effect of cultural intelligence on job satisfaction to employee performance at Bear Corps have relationship between cultural intelligence and job satisfaction. Here, the correlation between job satisfaction and employees performance have cultural intelligence and employees performance. Thus, the assessment has been performed using questionnaires to collect the observation data. Here, we use Structural Equation Model (SEM) modeling to examine the research model. The result shows, a stronger cultural intelligence will increase job employee satisfaction and strong job satisfaction will be encourage the employee performance